Building Borders in the City: The Turkish Government's Plan to “Dilute” the Migrant Presence in Urban Areas through the Example of the Altındağ Metropolitan District in Ankara - Pica, Cosimo (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2026)
This article intends to read the effects of European border externalization policies from the “south,” taking into consideration Turkey’s autonomy and local dynamics in bordering processes, which merge and intertwine with EU ones. Based on ethnographic fieldwork during 2022 and 2023 in the Altındağ metropolitan district of Ankara, I analyse how this urban borderland became the focal point of governmental practices and narratives after the anti-Syrian lynching that exploded in August 2021. An event that marked a new direction in the government’s migration policies with the issuing of the so-called “dilution plan” which establishes a maximum threshold of 20 % of foreign residents in the neighborhoods of metropolitan areas like Ankara and in 63 other provinces with a huge migrant presence. I maintain that the Turkish government’s “dilution plan” highlights how the border is above all a mobile threshold that marks a hierarchy between people within the same space, creating mechanisms of “differential inclusion”. With this study, I aim to discuss how bordering processes and practices not only reconfigure the Mediterranean space but also mark the urban spaces of the countries involved, such as Turkey.